Protein phosphorylation regulates secretion of Alzheimer beta/A4 amyloid precursor protein. - Caporaso, G L (1992)
Extracellular deposition of the beta/A4 amyloid peptide is a characteristic feature of the brain in patients with Alzheimer disease. beta/A4 amyloid is derived from the amyloid precursor protein (APP), an integral membrane protein that exists as three major isoforms (APP695, APP751, and APP770). Secreted forms of APP found in blood plasma and cerebrospinal fluid arise by proteolytic cleavage of APP within the beta/A4 amyloid domain, precluding the possibility of amyloidogenesis for that population of molecules. In the present study, we have demonstrated that treatment of PC12 cells with phorbol ester produces a severalfold increase in secretion of APP695, APP751, and APP770. This increase is augmented by simultaneous treatment with the protein phosphatase inhibitor okadaic acid. These data indicate that protein phosphorylation regulates intra-beta/A4 amyloid cleavage and APP secretion. These and other results suggest that APP molecules can normally follow either of two processing pathways: regulated secretion or proteolytic degradation unassociated with secretion.